Effect of continued treatment with pirfenidone following clinically meaningful declines in forced vital capacity: analysis of data from three phase 3 trials in patients with idiopathic pulmonary fibrosis. Issue 5 (11th March 2016) - Nathan, Steven D; Albera, Carlo; Bradford, Williamson Z; Costabel, Ulrich; du Bois, Roland M; Fagan, Elizabeth A; Fishman, Robert S; Glaspole, Ian; Glassberg, Marilyn K; Glasscock, Kenneth F; King, Talmadge E; Lancaster, Lisa; et al.
Abstract : Background: The assessment of treatment response in idiopathic pulmonary fibrosis (IPF) is complicated by the variable clinical course. We examined the variability in the rate of disease progression and evaluated the effect of continued treatment with pirfenidone in patients who experienced meaningful progression during treatment. Methods: The source population included patients enrolled in the ASCEND and CAPACITY trials (N=1247). Pearson's correlation coefficients were used to characterise the relationship between changes in FVC during consecutive 6-month intervals in the placebo population. Outcomes following a ≥10% decline in FVC were evaluated by comparing the proportion of patients in the pirfenidone and placebo groups who experienced a ≥10% decline in FVC or death during the subsequent 6 months. Results: A weak negative correlation was observed between FVC changes during consecutive intervals in the placebo population (coefficient, −0.146, p<0.001), indicating substantial variability. Thirty-four (5.5%) and 68 (10.9%) patients in the pirfenidone and placebo groups, respectively, experienced a ≥10% decline in FVC by month 6. During the subsequent 6 months, fewer patients in the pirfenidone group compared with placebo experienced a ≥10% decline in FVC or death (5.9% vs 27.9%; relative difference, 78.9%). There was one (2.9%) death in the pirfenidone group and 14 (20.6%) deaths in the placebo group (relative difference, 85.7%). Conclusions: Longitudinal FVC data from patients with IPF showed substantial intrasubject variability, underscoring the inability to reliably assess therapeutic response using serial FVC trends. In patients who progressed during treatment, continued treatment with pirfenidone resulted in a lower risk of subsequent FVC decline or death. Trial registration numbers: NCT01366209, NCT00287729, NCT00287716 .